The determinants of international trade in the new new theories of international trade - Sadek, Djamila; Derbal, Abdelkader (Finance and Business Economies Review, 2019)
International trade is one of the areas that has been and remains the concern of many economics researchers, particularly in recent times. This paper aims to highlight the most important determinants of international trade, within the framework of new "new" theories. Focusing on companies' export decisions and their behavior during offshoring and outsourcing. Productivity, type of industry, contract environment, research and development, production costs and other determinants of business behavior and export decisions are taken into account.